SHAPING WORKFORCE EXCELLENCE: THE ROLE OF AUTHENTIC LEADERSHIP IN EMPLOYEE TRAINING IN BANGLADESH’S BANKING SECTOR - Mendi Hassan Mirza (Academic Reseach Library for International Journal of Computer Science & Information System, 2025)
In Bangladesh’s commercial banking sector, effective employee training is essential for improving performance, service quality, and overall organizational success. Authentic leadership, characterized by transparency, integrity, and a strong commitment to employee development, plays a crucial role in shaping training effectiveness. This study examines the influence of authentic leadership on workforce training outcomes, exploring how leaders' trustworthiness, ethical behavior, and employee engagement impact learning retention and skill application. Through a combination of qualitative and quantitative analysis, the research highlights the positive correlation between authentic leadership and enhanced employee training effectiveness. Findings suggest that fostering an authentic leadership culture leads to higher motivation, better knowledge transfer, and improved job performance, ultimately strengthening the competitive edge of Bangladesh’s banking industry.